Thermal buckling and sound radiation behavior of truss core sandwich panel resting on elastic foundation. (October 2019) - Fu, Tao; Chen, Zhaobo; Yu, Hongying; Li, Chengfei; Zhao, Yanzheng
Highlights: The first order shear deformation theory and Reissner plate theory are used for analysis of thermal buckling and sound radiation behavior analyses of truss core sandwich structure resting on elastic foundation. The excellent accuracy of the established analytical model is demonstrated by comparisons with numerical simulation results calculated by commercial finite element software (LMS Virtual.Lab). Effects of the truss core radius, inclination angle and height, temperature field and elastic foundation stiffness coefficient on thermal buckling and sound radiation behavior are also investigated. A further comprehension was given on the underlying mechanism of sound radiation through lattice truss core sandwich plate structure under thermal environment. Abstract: Due to high stiffness and other potential multifunctional application characteristics, truss core sandwich structure offers a promising alternative to traditional stiffened or corrugated sandwich plates used in aerospace and marine industry. And sound radiation from plate structures is a design factor indicating the power reduction, which can help the lattice truss core sandwich structure meet the acoustic requirements for practical engineering design, but the sound radiation performance of this sandwich structure remains unclear. Based on that, the thermal buckling and sound radiation behavior analyses of truss core sandwich structure resting on elastic foundation in thermal environment are presented in this paper. The mechanical behavior of structure–foundation interaction is modeled as two-parameter model including Winkler and shear foundation. The sound radiation due to a concentrated harmonic force in thermal environment is computed by solving the Rayleigh integral. By comparing with numerical simulation results calculated by commercial finite element software, the accuracy and feasibility of theoretical model developed in this paper are validated. The effects of several key parameters including the truss core radius, inclination angle and height, temperature field and elastic foundation stiffness coefficient on thermal buckling and sound radiation behavior have been subsequently investigated. Graphical abstract: As a class of newly developed sandwich structures, lattice sandwich structures has attracted more and more researchers attention due to its potential multifunctional application characteristics. Through numerical results, we try to give a further comprehension of the underlying mechanism of acoustic response and to help the lattice truss core sandwich structure meet the acoustic requirements for practical engineering designImage, graphical abstract .